Structural optimization and in vivo evaluation of a colorectal stent with anti-migration and anti-tumor properties. (December 2022) - Cai, Simin; Jin, Zhu; Zeng, Ping; Yang, Lingxin; Yan, Yunqi; Wang, Zhongmin; Shen, Yuanyuan; Guo, Shengrong
Abstract: Clinically, colorectal stents can only palliatively relieve obstruction caused by colorectal cancer (CRC), with a high incidence of stent migration and tumor-related re-obstruction. To overcome these shortcomings, we developed a colorectal stent composed of a structure-optimized nitinol braided stent and a tubular film including an inner layer of poly (ethylene-co-vinyl acetate) (EVA) and a segmental outer layer of EVA with paclitaxel (PTX). The braiding pattern, segment number, and end shape of the stent were optimized based on the mechanical properties, ex vivo and in vivo anti-migration performance, and tissue response of the stent. The optimized nitinol stent had a structure of one middle segment in a hook-pattern and two end segments in a cross-pattern with two studs on each end in a staggered arrangement. Structure-optimized colorectal stents were prepared and evaluated in vivo . PTX released from the stent was mostly distributed in the rabbit rectum in contact with it. The biosafety of the colorectal stent was evaluated using blood tests, biochemical analysis, anatomical observation, and pathological analysis. The anti-tumor effect of the stent was also evaluated by endoscopy, anatomical observation, and pathological and immunohistochemical analyses in rabbits with orthotopic CRC. The results demonstrate that the optimized colorectal stents have effective anti-migration ability and anti-tumor effects with good biosafety. Statement of significance: In order to overcome the most common disadvantages of migration and re-obstruction of colorectal stents clinically, a colorectal stent composed of a structure-optimized nitinol stent and a tubular film including an inner layer of EVA and a segmental outer layer of EVA with PTX was put forward in this study. The optimized nitinol stent had a structure of one middle segment in hook-pattern and two end segments in cross-pattern with two studs on each end in staggered arrangement. The resulting colorectal stent has been proved with good anti-migration ability, anti-tumor effects, and biosafety in vivo, which provides a safe and effective potential treatment modality for patients with colorectal cancer. Graphical abstract: Image, graphical abstract